1998
DOI: 10.1063/1.367428
|View full text |Cite
|
Sign up to set email alerts
|

The role of structural relaxation in the plastic flow of metallic glasses

Abstract: The role of structural relaxation in the plastic flow behavior of metallic glasses is analyzed both theoretically and experimentally. The characteristic time of structural relaxation is calculated as a function of glass thermal prehistory. It is revealed that heating above the room temperature by several tens of Kelvins results in a sharp, by several orders of magnitude, decrease of this time. It is argued that localized “inhomogeneous” dislocation-like flow occurs on loading if the characteristic time of stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…In fact, this statement has been successfully proved using measurements of non-isothermal strain recovery [17] and acoustic emission [11 to 13] as fine indicators of the flow mode. It has been shown that under the strain rates of 10 À4 to 10 À6 s À1 this transition in samples preannealed at room temperature occurs slightly higher T 400 K [13] and, most likely, is independent of the glass chemical composition [17]. This result is in excellent agreement with the calculations of the relative SR rate for samples preannealed at room temperature (curve 1 in Fig.…”
Section: Sr Kinetics In the Load-free Statesupporting
confidence: 87%
See 2 more Smart Citations
“…In fact, this statement has been successfully proved using measurements of non-isothermal strain recovery [17] and acoustic emission [11 to 13] as fine indicators of the flow mode. It has been shown that under the strain rates of 10 À4 to 10 À6 s À1 this transition in samples preannealed at room temperature occurs slightly higher T 400 K [13] and, most likely, is independent of the glass chemical composition [17]. This result is in excellent agreement with the calculations of the relative SR rate for samples preannealed at room temperature (curve 1 in Fig.…”
Section: Sr Kinetics In the Load-free Statesupporting
confidence: 87%
“…If a glass is preannealed at a temperature T a during time t, cooled to a temperature T 0 and linear heating at a rate of T is started after that, it is easy to show that after heating during time t the RC volume spectral density will decrease to [13] …”
Section: Sr Kinetics In the Load-free Statementioning
confidence: 99%
See 1 more Smart Citation
“…There is also another argument leading to the same conclusion. In situ measurements of the acoustic emission in a metallic glass being deformed at different temperatures showed that the transition from homogeneous to inhomogeneous (localized) plastic flow is also controlled by the rate of structural relaxation but not by the homologous testing temperature [34].…”
Section: Viscoelastic Phenomenamentioning
confidence: 99%
“…The temperature dependence of r,, thus defined was calculated by Khonik et al (1998b). It was determined that this quantity is sharply dependent on the thermal pre-history, decreasing rapidly above the pre-annealing temperature.…”
Section: Internal Stressesmentioning
confidence: 99%